Sistem Penunjang Keputusan Pemilihan Sekolah Bersih Tingkat Sekolah Dasar Menggunakan Metode Simple Additive Weighting - Rusdi, Ibnu; Maria, Vivi (STMIK ANTAR BANGSA, 2018)
Abstract— The Special Capital Region of the Municipality of South Jakarta Administration is implementing the School Health Unit program for elementary school environment throughout South Jakarta in order to provide motivation and spirit to improve the cleanliness of the school environment and the participation of teachers and students by way of assessing the environment of elementary school area of South Jakarta Administration City. To determine the decision making in the elementary school hygiene assessment is accurate or not, an assessment should be done with the criteria that have been determined from the Sanitation Department of South Jakarta Administration City, other criteria needed in the assessment are cleanliness, physical facilities, facilities, greening and health services. The purpose of this research is to apply Simple Additive Weighting (SAW) as a decision support system in the determination of elementary school cleanliness in South Jakarta Cleanliness Sub-Department. Intisari— Daerah Khusus Ibukota (DKI) Kota Administrasi Jakarta Selatan menerapakan program bangun praja dan lomba Unit Kesehatan Sekolah (UKS) untuk lingkungan sekolah dasar seluruh wilayah Jakarta Selatan dalam rangka memberikan motivasi dan semangat untuk meningkatkan kebersihan dilingkungan sekolah dan peranserta para guru dan siswa/i masing-masing dengan cara melakukan penilaian dilingkungan sekolah dasar wilayah kota Administrasi Jakarta Selatan. Untuk mengetahui pengambilan keputusan dalam penilaian kebersihan sekolah dasar tersebut akurat atau tidak, harus dilakukan penilaian dengan kriteria yang telah ditentukan dari Dinas Kebersihan Kota Adminitrasi Jakarta Selatan, kriteria lain yang dibutuhkan dalam penilaian adalah kebersihan, sarana fisik, fasilitas, penghijauan dan pelayanan kesehatan. Tujuan dari penelitian adalah menerapkan Simple Additive Weighting (SAW) sebagai sistem pendukung keputusan dalam penetuan penilaian kebersihan sekolah dasar di Suku Dinas Kebersihan DKI Jakarta Selatan. Kata Kunci— Decision Support System, School Clean, Simple Additive Weighting